Modeling protoplanetary disk evolution in young star forming regions. Issue Volume 16:Issue S362(2020) (June 2020) - Wilhelm, Martijn J. C.; Portegies Zwart, Simon; Cournoyer-Cloutier, Claude; Lewis, Sean; Polak, Brooke; Tran, Aaron; Mac Low, Mordecai-Mark; McMillan, Stephen L. W.
Abstract: Stars form in clusters, while planets form in gaseous disks around young stars. Cluster dissolution occurs on longer time scales than disk dispersal. Planet formation thus typically takes place while the host star is still inside the cluster. We explore how the presence of other stars affects the evolution of circumstellar disks. Our numerical approach requires multi-scale and multi-physics simulations where the relevant components and their interactions are resolved. The simulations start with the collapse of a turbulent cloud, from which stars with disks form, which are able to influence each other. We focus on the effect of extinction due to residual cloud gas on the early evolution of circumstellar disks. We find that this extinction protects circumstellar disks against external photoevaporation, but these disks then become vulnerable to dynamic truncation by passing stars. We conclude that circumstellar disk evolution is heavily affected by the early evolution of the cluster.